PENGARUH KEPUASAN KELUARGA TERHADAP INTENSI BERHENTI DARI PEKERJAAN - Musadieq, Mochammad Al (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
This study aims to test how much influence family satisfaction of the interest to stop the work of the officers of private Fire Disaster Reduction. To get the conclusion of research, which analisisdata method diguanakan in this research is analysis descriptive statistics and inferential statistical analysis (regression analysis). The research analysis toward 107 respondents by using regression analysis resulted that intention to quit is negatively but insignificantly influenced by family satisfaction. This result is inconsistent with the findings of previous study by Lee dan Maurer (1999), Haar (2004), and Joseph (2007).